THE SCIENTIFIC INTEGRATION OF SOCIOLOGY IN ISLAMIC STUDIES: A THEORETICAL AND APPLICATIVE ANALYSIS - Syihabuddin, Muhammad; Manggala, Kayan; Ansharah, Indana Ilma; Nurkholisoh, Siti (CV. Fahr Publishing, 2024)
This article explores the scientific integration of sociology in Islamic studies through theoretical and applicative analysis. This research aims to understand how sociological principles can be applied in Islamic studies to enrich insights and methods in understanding religious social dynamics. Using a qualitative approach, this article analyzes various relevant sociological theories and their applications in the Islamic context, such as functional structural theory, conflict theory, and other social theories. The results show that this integration not only broadens the academic perspective but also significantly contributes to understanding and addressing social issues in Muslim societies. The article also suggests some practical strategies for applying these findings in Islamic teaching and research to generate more comprehensive and inclusive insights. The scientific integration of sociology in Islamic studies is very close because studying Islam cannot escape the social and religious phenomena that surround it. Therefore, the study of Islam or the study of Islam will be easier to understand if it is passed with various approaches, one of which is a sociological approach.